Chloromethane emissions in human breath - Keppler, Frank; Fischer, Jan; Sattler, Tobias; Polag, Daniela; Jäger, Nicole; Schöler, Heinz Friedrich; Greule, Markus (The science of the total environment, 2017)
Chloromethane (CH3Cl), currently the most abundant chlorinated organic compound in the atmosphere at around ~550 parts per trillion by volume (pptv), is considered responsible for approximately 16% of halogen-catalyzed stratospheric ozone destruction. Although emissions of CH3Cl are known to occur from animals such as cattle, formation and release of CH3Cl from humans has not yet been reported. In this study a pre-concentration unit coupled with a gas chromatograph directly linked to a mass spectrometer was used to precisely measure concentrations of CH3Cl at the pptv level in exhaled breath from 31 human subjects with ages ranging from 3 to 87years. We provide analytical evidence that all subjects exhaled CH3Cl in the range of 2.5 to 33 parts per billion by volume, levels which significantly exceed those of inhaled air by a factor of up to 60. If the mean of these emissions was typical for the world's population, then the global source of atmospheric CH3Cl from humans would be around 0.66Ggyr−1 (0.33 to 1.48Ggyr−1), which is less than 0.03% of the total annual global atmospheric source strength. The observed endogenous formation of a chlorinated methyl group in humans might be of interest to biochemists and medical scientists as CH3Cl is also known to be a potent methylating agent and thus, could be an important target compound in future medical research diagnostic programs.